2001
DOI: 10.1080/01443610020025976
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum hysterectomy in the 1990s: any new lessons?

Abstract: We aimed to identify the risk factors and subsequent maternal and perinatal outcome associated with the procedure of peripartum hysterectomy. This was a retrospective case review carried out at the National Maternity Hospital, Dublin, of all patients who underwent a peripartum hysterectomy from January 1990 to December 1999. Seventeen cases were performed during the study period from a total of 64 563 deliveries (0.03%). Mean maternal age was 34 years (21-43). There were no nulliparous patients. Eight patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…23,24 However, in cases of morbidly adherent placenta total hysterectomy may prove more beneficial as removal of the cervix leads to better hemostasis. 25 In our study, eight cases underwent total hysterectomy. Seven of these cases were those of morbidly adherent, low lying placenta and one case was of uterine rupture.…”
Section: Discussionmentioning
confidence: 78%
“…23,24 However, in cases of morbidly adherent placenta total hysterectomy may prove more beneficial as removal of the cervix leads to better hemostasis. 25 In our study, eight cases underwent total hysterectomy. Seven of these cases were those of morbidly adherent, low lying placenta and one case was of uterine rupture.…”
Section: Discussionmentioning
confidence: 78%
“…A study performed in Nigeria in 2012 found that the rate of EPH was 4.0 per 1000 deliveries 9 . The rate is lower in European countries: a rate of 0.2 per 1000 births was reported from Norway, 10 and 0.3 per 1000 births from Ireland 11 and the Netherlands 12 . This may be because of proper use of effective prenatal and delivery facilities, and the desire for small family size in Europe 11–14 …”
Section: Introductionmentioning
confidence: 99%
“…12 This may be because of proper use of effective prenatal and delivery facilities, and the desire for small family size in Europe. [11][12][13][14] In Ethiopia, hemorrhage has been the leading cause of mortality in recent years, followed by hypertensive disorders of pregnancy and sepsis, whereas the contributions of obstructed labor/uterine rupture and abortion have decreased over the same period. 15 Although the causes of maternal mortality are well studied in Ethiopia, there are no data on incidence and maternal outcomes of EPH.…”
mentioning
confidence: 99%
“…[123] Cesarean delivery is the major risk factor for peripartum hysterectomy and due to recently raising cesarean delivery rate and the increasing population with a scarred uterus, the incidence of emergency peripartum hysterectomy may indirectly increase. Historically, the most common indication cited for peripartum hysterectomy was uterine atony[456789] but, more recent reports have suggested that abnormal placentation, including placenta accreta, has become the most common indication for peripartum hysterectomy. [1011]…”
Section: Introductionmentioning
confidence: 99%